2011
DOI: 10.1590/s0100-83582011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Efeito alelopático do fruto de Sapindus saponaria na germinação e na morfologia de plântulas daninhas e de hortaliças

Abstract: RESUMO -O objetivo deste estudo foi avaliar o potencial alelopático do extrato aquoso de frutos de Sapindus saponaria (sabão-de-soldado) na germinação de diásporos e na morfologia de plântulas de Lactuca sativa (alface), Allium cepa (cebola), Echinochloa crus-galli (capim-arroz) e Ipomoea grandifolia (corda-de-viola). O extrato aquoso dos frutos foi preparado na proporção de 100 g de material vegetal fresco para 1.000 mL de água destilada, produzindo-se a concentração de 10%. A partir dele, foram feitas diluiç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
7
0
4
Order By: Relevance
“…In phytochemical prospecting for the detection of organic acids in shoot fractions of U. humidicola, only low intensity signals were detected in the ethyl ace- for the present study, saponins also have allelopathicaction [26]. Thiswas indicated by the negative effects of the saponins isolated from the root extracts of U. humidicola on the germination of L. sativa and M. axillare compared to the control ( Figure 9).…”
Section: Discussionmentioning
confidence: 54%
“…In phytochemical prospecting for the detection of organic acids in shoot fractions of U. humidicola, only low intensity signals were detected in the ethyl ace- for the present study, saponins also have allelopathicaction [26]. Thiswas indicated by the negative effects of the saponins isolated from the root extracts of U. humidicola on the germination of L. sativa and M. axillare compared to the control ( Figure 9).…”
Section: Discussionmentioning
confidence: 54%
“…Houve decréscimo linear na porcentagem de germinação, na velocidade média de germinação e na velocidade de germinação. Por outro lado, houve aumento linear no tempo médio de germinação (41) . Em bioensaios realizados com extratos foliares das espécies Peltophorum dubium e Psychotria leiocarpa, igualmente constataram que os extratos causaram atraso na germinação dos aquênios L. sativa, o que foi visualizado nas alterações do tempo médio de germinação (53) , assim como observado em nossos estudos.…”
Section: Resultados E Discussõesunclassified
“…A preparação do extrato realizou-se seguindo uma metodologia adaptada (41) , utilizada nos bioensaios de germinação. Folhas de H. speciosa sadias foram retiradas de forma assistemática, de dez matrizes préselecionadas de cada área.…”
unclassified
See 1 more Smart Citation
“…The radicle of the emerged plants in the concentrations used was the most affected structure by the aqueous extract of L. auriculata root, because 100% showed reduced size, deformation and/or necrosis. Grisi et al (2011), in a study conducted on the allelopathic effect of Sapindus saponaria morphology, found that the reduction in size and necrosis were the most common symptoms in the roots of the seedlings treated with the donor plant extract. In the same study, the authors found that lettuce seedlings showed reduced growth of the primary root, reaching zero values when subjected to the concentration of 7.5%.…”
Section: Aqueous Extract Of Roots L Auriculatamentioning
confidence: 99%